Quercus infectoria Gall Ethanolic Extract Accelerates Wound Healing through Attenuating Inflammation and Oxidative Injuries in Skin Fibroblasts - Suttiwan Wunnoo; Decha Sermwittayawong; Rachanida Praparatana; Supayang Piyawan Voravuthikunchai; Chanawee Jakkawanpitak (MDPI AG, 2024)
Quercus infectoria Olivier (Fagaceae) nutgall, a traditional Asian medicine, is renowned for its efficacy in treating wounds and skin disorders. Although the gall extract has shown promising results in accelerating wound healing in diabetic animal models, its mechanisms, particularly the effects on redox balance, remain poorly understood. This study aims to investigate the effects and mechanisms of Q. infectoria gall ethanolic extract (QIG) on wound healing in fibroblasts, with a specific emphasis on its modulation of oxidative stress. Hydrogen peroxide (H2O2)-treated L929 cells were used as an in vitro model of oxidation-damaged fibroblasts. QIG exhibited potent antioxidant activity with 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid (ABTS), and ferric reducing antioxidant power (FRAP) assay values of 305.43 ± 7.48, 508.94 ± 15.12, and 442.08 ± 9.41 µM Trolox equivalents (TE)/µg, respectively. Elevated H2O2 levels significantly reduced L929 cell viability, with a 50% lethal concentration of 1.03 mM. QIG mitigated H2O2-induced cytotoxicity in a dose-dependent manner, showing protective effects in pre-, post-, and co-treatment scenarios. QIG significantly reduced H2O2-induced intracellular reactive oxygen species production and inflammation-related gene expression (p < 0.05). Additionally, at 25 µg/mL, QIG remarkably improved wound closure in H2O2-treated L929 cells by approximately 9.4 times compared with the H2O2 treatment alone (p < 0.05). These findings suggest QIG has potential therapeutic applications in wound healing, mediated through the regulation of oxidative stress and inflammatory response.